2014
DOI: 10.1016/j.jtcvs.2013.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Current era minimally invasive aortic valve replacement: Techniques and practice

Abstract: Surgeons interested in learning and performing minimally invasive aortic valve replacement must have expertise in conventional aortic valve replacement at centers with adequate case volumes. A team approach that coordinates efforts of the surgeon, anesthesiologist, perfusionist, and nurses is required to achieve the best clinical outcomes. By first developing fundamental minimally invasive skills using specialized cannulation techniques, neck lines, and long-shafted instruments in the setting of conventional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 19 publications
0
98
1
7
Order By: Relevance
“…A recent study reported the achievement of operative field exposure using pericardial traction and fixation to the skin edge during minimally invasive aortic valve surgery. 16) We exposed the operative field using pericardial traction with a rib retractor, which provided a good operative field by pulling the right heart. One of our patients had severe adhesions caused by bone fractures, and pericardial traction could not provide a good operative field and may have led to paravalvular leakage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the achievement of operative field exposure using pericardial traction and fixation to the skin edge during minimally invasive aortic valve surgery. 16) We exposed the operative field using pericardial traction with a rib retractor, which provided a good operative field by pulling the right heart. One of our patients had severe adhesions caused by bone fractures, and pericardial traction could not provide a good operative field and may have led to paravalvular leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal invasive AVR has several advantages such as shorter length of stay [1,2,3,5,6,8] shorter duration of ventilation [1,2,6,8], decreased time until return to full activity [2], improved cosmetics [4,8,10], decreased rate of postoperative renal failure [5] and less postoperative pain [8] compared with conventional AVR. A recent meta-analysis found no significant difference between AVR and MAVR for postoperative atrial fibrillation, myocardial infarctions, pneumonia, pneumothorax, sternal/wound infections or mortality rate [3].…”
Section: M-avrmentioning
confidence: 99%
“…Compared to conventional sternotomy for aortic valve replacement (AVR), M-AVR diminishes postoperative ventilation time, reduces pain, hospital length of stay, time until return to full activity, and decreases use of blood products [1][2][3][4][5][6][7][8][9][10].Although M-AVR has a mortality rate comparable to conventional AVR [1][2][3][4][5][6][7][8], one of the main obstacles of M-AVR is the increased cardiopulmonary bypass (CPB) and aortic cross-clamping time [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…У больных, перенесших вмешательства на АК через мини-стернотомию или миниторакотомию, достоверно меньше послеоперационная кровопотеря, потребность в перели-вании компонентов крови, сроки нахождения в отделе-нии реанимации и стационаре, менее выраженный боле-вой синдром и ниже частота осложнений со стороны гру-дины, послеоперационной раны [2,3,5,6,8].…”
unclassified
“…В некоторых клиниках мира до-ля подобных вмешательств достигает 65% [2,8]. Очевид-но, что более половины пациентов могут быть проопери-рованы через минидоступ.…”
unclassified